2014
DOI: 10.1590/s0036-46652014000600003
|View full text |Cite
|
Sign up to set email alerts
|

SEROLOGICAL AND MOLECULAR SURVEY OF Leptospira spp. AMONG CART HORSES FROM AN ENDEMIC AREA OF HUMAN LEPTOSPIROSIS IN CURITIBA, SOUTHERN BRAZIL

Abstract: Introduction: Cart horses are a re-emerging population employed to carry recyclable material in cities. Methods: Sixty-two horses were sampled in an endemic area of human leptospirosis. The microscopic agglutination test (MAT) and real-time polymerase chain reaction (qPCR) were performed. Results: A seropositivity of 75.8% with serovar Icterohaemorrhagiae in 80.8% of the horses was observed. Blood and urine were qPCR negative. MAT showed positive correlations with rainfall (p = 0.02) and flooding (p = 0.03). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 7 publications
2
25
1
6
Order By: Relevance
“…Leptospirosis is a wellknown ailment of horses, with significant clinical and reproductive repercussions (Tadich et al 2016). Our study shows that draft horses in urban settings are particularly exposed to the disease, with a seroprevalence of 28.57%, compared to other populations of the same region (Finger et al 2014). To our knowledge, this is the first study in Brazil to focus on this population.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Leptospirosis is a wellknown ailment of horses, with significant clinical and reproductive repercussions (Tadich et al 2016). Our study shows that draft horses in urban settings are particularly exposed to the disease, with a seroprevalence of 28.57%, compared to other populations of the same region (Finger et al 2014). To our knowledge, this is the first study in Brazil to focus on this population.…”
Section: Discussionmentioning
confidence: 63%
“…In southernmost Brazil, equine leptospirosis varies greatly. Studies that considered draft horses in urban settings show prevalences of 60% and 75% (Finger et al 2014;Lasta et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An even higher prevalence of antibodies against Leptospira spp. was observed in cart horses (75.8%), also with Icterohaemorrhagiae as the most frequent serogroup (80.8%) (Finger et al 2014). In this area, poor sanitary conditions and infrastructure, proximity to garbage dump sites and open sewers and flooding were associated to seroprevalence of leptospirosis (Bier et al 2012, Finger et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…was observed in cart horses (75.8%), also with Icterohaemorrhagiae as the most frequent serogroup (80.8%) (Finger et al 2014). In this area, poor sanitary conditions and infrastructure, proximity to garbage dump sites and open sewers and flooding were associated to seroprevalence of leptospirosis (Bier et al 2012, Finger et al 2014). Since Vila Pantanal and Curitiba zoo are both located in Iguaçu Municipal Park and Iguaçu River go through them, it may be considered that animals from both places are submitted to the same environmental conditions and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome all these limitations polymerase chain reaction (PCR) have been used, which is considered sensitive and specific for the rapid detection of Leptospira in clinical samples. Evaluation of PCR-based studies for the identification and diagnosis of leptospirosis has been reported elsewhere, in humans and animals [13,28,29,30]. It has been developed for the rapid detection of Leptospira DNA and has the potential to make a dramatic impact in diagnosing leptospirosis [25].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%